Si3.5Sb2Te3 Phase Change Material for Low-Power Phase Change Memory Application - 任堃 饶峰 宋志棠 吴良才 周夕淋 夏梦娇 刘波 封松林 席韡 姚栋宁 陈邦明 (Chinese physics letters, 2010)
Novel Si3.5Sb2Te3 phase change material for phase change memory is prepared by sputtering of Si and Sb2Te3 alloy targets. Crystalline Si3.5Sb2Te3 is a stable composite material consisting of amorphous Si and crystalline Sb2Te3, without separated Te phase. The thermally stable Si3.5Sb2Te3 material has data retention ability （10 years at 412K） better than that of the Ge2Sb2Te5 material （10 years at 383 K）. Phase change memory device based on Si3.5Sb2Te3 is successfully fabricated, showing low power consumption. Up to 2.2 × 107 cycles of endurance have been achieved with a resistance ratio lager than 300.